A is for algorithm. (Economist, 2014)
The article focuses on a global demand for increased computer science education. It states that the advent of graphical user interfaces and ready-made applications in the 1980s saw a shift from teaching computer coding to information and communications technology and reflects on a shortage of skilled programmers. It compares Britain's computer science education system to that of Bavaria and Israel and claims Britain is skimping and has introduced its new curriculum in a rush.